ISOLASI, SELEKSI DAN KARAKTERISASI BAKTERI ASAM LAKTAT PENGHASIL SENYAWA ANTIBAKTERI PADA TELUR ASIN - , KURNIAWAN EKA SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Lactic acid bacteria widely found in Indonesian tradisional food. Salted egg is one of traditional foods using spontaneous fermentation techniques, with salt as fermentation media. Spontaneous fermentation will create the diversity of microorganism and which actively play a role will grow optimum. Aim of this study is to isolate and characterize lactic acid bacteria from salted egg, with 3 parts used, i.e egg white, shell and dough (red brick powder, rub ash, and salt). The isolates will be selected through the inhibitory ability against pathogenic bacteria, namely Eschericia coli and Staphylococcus aureus. The main materials used for this study were salted egg (egg white, shell, and dough), MRS media for isolation and purification, MHA for antibacterial activity test, and Yeast-Pepton for acid production testing. The analysis were testing and observation of cells and colonies morphology, antibacterial activity test using agar-well diffusion method, physiology test for effect of temperature salt concentration and pH on bacteriaâs ability to grew in the media, and characteristic test to determine the genus and species of lactic acid bacteria isolated. The results are 43 isolated were obtained, with 14 isolates had the best antibacterial abilities. One isolate with code C54 produced bacteriocin and 13 isolates inhibited by organic acid produced. Five isolates on the part of dough, 4 isolates on eggwhite, and 5 isolates on shell. All isolates were gram-positive, catalase negative, non-motile, and homofermentative. The species obtained were 5 isolates for Lactobacillus plantarum, 6 isolates for Lactobacillus casei subsp. rhamnosus and Enterococcus gallinarum, and 2 isolates for Pediococcus acidilactici.